STRATEGI LITERASI DIGITAL: TRANSFORMASI PERAN DARI PENGGUNA KE KREATOR KONTEN MEDIA SOSIAL - Siti Nurannisaa Parama Bekti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Social media has become an integral part of adolescents’ lives, including junior high school students. However, many students still use social media merely as a form of entertainment, without recognizing its potential as a medium for digital literacy development, self-expression, and education. Digital literacy equips students with the ability to understand technology, build communities, enhance engagement, and create opportunities for creativity and economic participation. This community service program was designed to equip junior high school students with creative digital literacy skills, enabling to transform from users into creators through practice-based training. The implementation employed an experiential learning approach, in which students were directly involved in the planning and production of digital content. The training was conducted in a single intensive session integrating three core materials: content planning based on content pillars, basic photography techniques using smartphones, and short video production through simple mobile applications. Throughout the activity, students were encouraged to actively take on the roles of designers and creative content talents, developing themes relevant to their school environment and positive values. Through this program, students are not only trained technically, but also equipped with the knowledge to become designers and productive digital talents.The results show that 76.5% of students exhibited a shift in mindset, placing greater value on the process behind content creation and showing a greater willingness to compromise on time or energy to achieve better outcomes. The evaluation of the students' work indicates their ability to produce simple content that combines inspirational messages with well-executed visual techniques. Presentations displayed a variety of creativity, ranging from educational themes to light entertainment relevant to school life. This program can serve as a model to strengthen students' literacy, fostering a productive digital character. ABSTRAK Media sosial telah menjadi bagian penting dalam kehidupan remaja, termasuk siswa Sekolah Menengah Pertama (SMP). Namun, sebagian siswa masih menggunakan media sosial hanya sebagai sarana hiburan tanpa memahami potensi positif sebagai media pengembangan literasi digital, ekspresi, dan edukasi. Literasi digital membantu siswa memahami cara penggunaan teknologi, membangun komunitas, meningkatkan keterlibatan, menciptakan peluang kreasi, dan ekonomi. Kegiatan Pengabdian kepada Masyarakat (PKM) ini dirancang untuk membekali siswa SMP dengan kemampuan literasi digital kreatif dari pengguna menjadi kreator melalui pelatihan berbasis praktik. Metode pengabdian menggunakan pendekatan experiential learning, siswa terlibat langsung dalam proses perencanaan dan produksi konten digital. Pelatihan dilakukan dalam satu kali pertemuan intensif, dengan integrasi tiga materi utama: perencanaan konten berbasis content pillar, teknik fotografi dasar menggunakan ponsel, dan pembuatan video pendek dengan aplikasi mobile sederhana. Dalam pelaksanaan kegiatan, siswa didorong untuk aktif berperan sebagai desainer dan talent kreator konten, dengan tema yang relevan dengan lingkungan sekolah dan nilai-nilai positif. Melalui kegiatan ini, siswa tidak hanya dilatih secara teknis, namun pengetahuan sebagai desainer, digital talent yang produktif. Hasil menunjukkan 76.5% memiliki perubahan pola pikir yang lebih menghargai proses di balik pembuatan konten, dan lebih siap untuk berkompromi dengan waktu atau energi demi mencapai hasil yang lebih baik. Hasil evaluasi karya yang dibuat siswa menunjukkan kemampuan memproduksi konten sederhana yang memadukan pesan inspiratif dengan teknik visual yang rapi. Presentasi memperlihatkan variasi kreativitas, mulai dari konten bertema edukasi hingga hiburan ringan yang relevan dengan kehidupan sekolah. Kegiatan dapat menjadi model guna memperkuat literasi siswa untuk memperkuat karakter digital yang produktif.